A comparison of the peri-implant bone stress generated by the preload with screw tightening between 'bonded' and 'contact' model. Issue 4 (12th March 2017) - Matsuzaki, Maki; Ayukawa, Yasunori; Sakai, Nobuo; Matsuzaki, Tatsuya; Matsushita, Yasuyuki; Koyano, Kiyoshi
Abstract: A number of finite element analyses (FEAs) for the dental implant were performed without regard for preload and with all interfaces 'fixed-bonded'. The purpose of this study was comparing the stress distributions between the conventional FEA model with all contacting interfaces 'fixed-bonded' (bonded model) and the model with the interfaces of the components in 'contact' with friction simulated as a preloaded implant (contact model). We further verified the accuracy of the result of the FEA using model experiment. In the contact model, the stress was more widely distributed than in the bonded model. From the model study, the preload induced by screw tightening generated strain at the peri-implant bone, even before the application of external force. As a result, the bonded model could not reproduce the mechanical phenomena, whereas the contact model is considered to be appropriate for analysing mechanical problems.